Bank Size and Risk-Taking under Basel II - Hendrik Hakenes; Isabel Schnabel (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We analyze the relationship between bank size and risk-taking under the New Basel Capital Accord. Using a model with imperfect competition and moral hazard, we show that the introduction of an internal ratings based (IRB) approach improves upon flat capital requirements if the approach is applied uniformly across banks and if the costs of implementation are not too high. However, the banks' right to choose between the standardized and the IRB approaches under Basel II gives larger banks a competitive advantage and, due to fiercer competition, pushes smaller banks to take higher risks. This may even lead to higher aggregate risk-taking.
urn:nbn:de:bvb:19-epub-13463-0
Keywords: G21; G28; L11; 330; Basel II; IRB approach; bank competition; capital requirements; SME financing